1993
DOI: 10.1002/stem.5530110412
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine transforming growth factor β1 blocks colony formation and progenitor cell generation by hemopoietic stem cells stimulated with steel factor

Abstract: The ability of Steel Factor (SF) to stimulate colony formation and progenitor cell generation by hemopoietic stem cells (HSCs) in vitro in the absence of interleukin 3 (IL-3) was investigated. IL-3 was required for HSC proliferation, and no or restricted proliferation occurred in the presence of SF, IL-6, IL-11, or IL-12 as single factors or in combination. Neutralizing concentrations of anti-transforming growth factor (TGF)-beta 1 antibodies enhanced progenitor cell generation 2-3-fold in the presence of IL-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
(7 reference statements)
3
30
0
Order By: Relevance
“…4 During retroviral gene transfer, there are a number of potential sources of deleterious TGF-␤, including autocrine production by primitive target cells, paracrine production by other marrow hematopoietic elements such as stromal cells, or release of TGF-␤ by retroviral producer cell lines into supernatants used for transduction. 9,11,38 Increased retroviral gene transfer efficiency into committed progenitor cells after abrogation of TGF-␤ activity with antisense oligonucleotides or a neutralizing antibody has been previously reported. 17,38 Our report is the first to document improved retroviral gene transfer into long-term repopulating cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 During retroviral gene transfer, there are a number of potential sources of deleterious TGF-␤, including autocrine production by primitive target cells, paracrine production by other marrow hematopoietic elements such as stromal cells, or release of TGF-␤ by retroviral producer cell lines into supernatants used for transduction. 9,11,38 Increased retroviral gene transfer efficiency into committed progenitor cells after abrogation of TGF-␤ activity with antisense oligonucleotides or a neutralizing antibody has been previously reported. 17,38 Our report is the first to document improved retroviral gene transfer into long-term repopulating cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 TGF-␤ are produced by marrow microenvironmental components such as stromal cells and macrophages, as well as by primitive hematopoietic progenitors themselves. [9][10][11]21,26,27 Abrogation of autocrine or paracrine TGF-␤ with a neutralizing antibody or specific antisense oligonucleotides can improve the viability and proliferative potential of ex vivo cultured primitive hematopoietic cells. 9,11,21,[26][27][28][29] We have previously shown that true murine repopulating stem cell activity as measured by the quantitative murine competitive repopulation assay is also increased two-to four-fold by inclusion of neutralizing TGF-␤ antibody during culture in IL-3, IL-6 and SCF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that TGF-β1 was consistently associated with hematopoietically active tissues had clear implications of its involvement in hematopoiesis. It has even been observed that TGF-β1 could be an activator [36][37][38] or inhibitor [32,33,[39][40][41][42][43][44][45] of hematopoiesis, depending on the target population. The activatory role of TGF-β1 in these experiments was confined only to GM progenitors and required that higher concentrations of TGF-β1 (ng/ml) be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have found these cytokine combinations to synergize in progenitor cell generation and colony formation of murine bone marrow cells, 12,13 and to be extremely useful for detecting the presence of very low concentrations of TGF-␤1 (ie down to 1 pg/ml). 14,15 From Figure 1 it appears that BMP-9 concentrations of 100 ng and higher, completely abrogated CFU-C generation stimulated by SF+IL-12, and almost completely when low concentrations of IL-3 (5 U) were included. The same effect could be observed if IL-12 was replaced by IL-11 (data not shown).…”
Section: Bmp-9 Inhibits Cfu-c Generation In Lcmentioning
confidence: 97%